Pengembangan Media Adobe Animate Berbasis PBLPembelajaran Matematika Materi Bangun Ruang Kelas V Sekolah Dasar - Kharismawati, Annisa'; Nugraheni, Nursiwi (Program Studi Pendidikan Matematika FIP UNHASY, 2025)
The low interest and learning outcomes of class V students at SDN Pringsari 02 in mathematics subjects, especially in cube and block geometric material, is the main problem in the learning process. This is caused by the limited interactive learning media and conventional teaching approaches. This research aims to develop learning media based on Problem Based Learning (PBL) using Adobe Animate, as well as testing the feasibility and effectiveness of this media in improving students' understanding of mathematical concepts. The research method used was the Borg and Gall Research and Development (R&D) model which was modified into eight stages. The test subjects consisted of 6 students (small scale) and 28 students (large scale). Data collection techniques include observation, interviews, questionnaires, documentation, as well as pretest and posttest. Expert validation results show that the media is very suitable for use (average suitability 90%). The effectiveness test showed a significant increase in learning outcomes through the t test (t-count = 11.877) and N-Gain of 0.557 (medium category). The conclusion of this research is that PBL-based Adobe Animate media is effective in improving student learning outcomes and interest. The novelty of this research lies in the integration of interactive animation media Adobe Animate with the PBL approach in elementary school level mathematics learning.